Performance evaluation of a venous valve - Koh, Yun Yao (Nanyang Technological University, 2021)
Chronic venous insufficiency (CVI) is a condition whereby the venous valves fail to function as intended and this results in retrograde blood flow. This affects the efficiency of blood flowing from the lower extremities of the human limbs back to the heart. Therefore, there is a need to design a venous valve test rig that could be used to examine the design of new prosthetic venous valves that would replace the damaged venous valves. In this report, the steps to modify and redesign various aspects of the original setup would be conducted so that a more suitable setup could be used as a test rig for venous valve design. Results from this project show that the setup can compress the conduit with a slight expansion of the chamber to account for the flexibility of muscles. In this project, the chamber is redesigned, and silicon sheets are used to mimic the flexibility of human muscles during compression and expansion. Various features of the project have also been changed to refine the design of the previous setup. However, there remains some improvements to be made to further optimise the setup.